Crisis intervention for children in school (in post-Traumatic stress disorder). (Journal of Educational Sciences, 2016)
In the article briefl y describes one of the interesting phenomena of the consequences of the crisis situation for the children, namely – PTSD. PTSD in children is regarded as a controversial diagnosis, uniting not only the etiological factors and experienced a traumaticevent, but the adverse situation of personal experience, which can be quite diverse. In spite of the fact that the distress in children occurs with symptoms similar to symptoms in adults, it has its own specifi cs and tools for assessment.
Keywords: crisis intervention; professional work of the teacher; the teacher of the school; psychological preparation of school teachers; post-traumatic stress disorder